Integration of Biblical and Pastoral Approaches in Dealing with Alcohol and Drug Abuse in the Presbyterian Churches of Kenya - Mathai, Lucy Mutare (International Journal of Culture and History, 2024)
Global statistics show persistence of alcohol and drug abuse despite the programmes religious organisations have come up with aimed at mitigating alcohol and drug abuse. This study analyzed the Biblical and pastoral approaches used by Presbyterian Churches (PCEA) in addressing the problem of alcohol and drug abuse. Multistage Cluster sampling technique was used to select three PCEA regions from the five regions. The study had a total sample of 144 respondents who were the Parish ministers. A descriptive survey research design was used to obtain qualitative data. Instrument for data collection was structured interview schedule. Data collected from the Parish ministers was analyzed qualitatively. The study established that the Presbyterian churches integrated both Biblical and pastoral approaches in mitigating alcohol and drug abuse. Majority of the parish ministers indicated that they used sermons as a pastoral intervention for alcohol and drug abuse among the youth in the Presbyterian churches. Other pastoral interventions included pastoral counseling, open discussions on alcohol and drugs and praying for the addicts. Parish ministers also indicated that they used the Bible to warn against the use of alcohol and more specifically its intoxicating effect and this justifies why the church should get involved in the lives of those abusing alcohol and drugs so as to help them get out of the bondage. The Bible commends self-control with regard to alcohol. Parish ministers used Bible verses to explain that the Bible forbids participating for the sake of personal pleasure, in practices that hinder moral judgment or weaken self-control. The findings of this study will help the clergy to address problem of alcohol and drug abuse in the society and particularly among the youth as this segment of the population is vital for church and societal development.